E-Pop Up Book of Stories on Hindu-Buddhist Kingdoms to Improve Elementary Students’ Learning Outcomes - Dewa Ayu Nita Maharani; Basilius Redan Werang; Syafitri Br. Ginting (Universitas Pendidikan Ganesha, 2025)
The low interest and learning outcomes of elementary school students in history material are problems that need to be addressed with interesting learning media. The material on the Hindu-Buddhist Kingdoms is often considered boring and difficult to understand because it is delivered conventionally without the support of interactive visual media. This study aims to develop a story-based e-pop-up book media on the material on the Hindu-Buddhist Kingdoms to improve student learning outcomes. The method used is development research with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The developed media was tested on 21 fifth-grade elementary school students. The data collection method used observation, interview and document study techniques. The data analysis techniques used were normality, homogeneity and correlation t-test. The results of the study showed that the use of e-pop-up books can improve students' understanding and interest in history material. The conclusion of this study is that e-pop-up story books are effective as learning media to improve student learning outcomes on the material on the Hindu-Buddhist Kingdoms. The implication of this finding is that teachers can utilize interactive digital media as an innovative alternative in history learning at the elementary school level.